Savings and economic diversification among youth in Ghana: implications for policy and practice - Gilbert Dagunga; Shaibu B. Azumah; Abraham Zakaria; Nathaniel A. Boateng; Kwadwo B. Mensah; Ethel Seiwaa Boateng; Emile M. Tsekpo; Philip Kankam (Cogent Economics & Finance, 2022)
Savings remain a critical mechanism for capital accumulation for the purpose of investment in developing countries like Ghana. Using data from the Next Generation Cocoa Youth Programme (MASO) implemented by Solidaridad and partners, a bias correcting count data model was applied to determine the drivers of savings, and the impact of savings on youth economic diversification. The results showed that youth trust on financial institutions as well as usage of mobile phones for digital marketing have a positive and significant effect on their decision to save at 1% significance level. The parametric results revealed a significant positive impact of savings on youth economic diversification at 1% significance level. There is thus the need for the promotion of savings among the youth as a tool by national youth policy to reduce youth unemployment in Ghana.
Keywords: 330; Economic diversification; Endogenous switching Poisson; MASO Programme; Savings; Youth